EKSISTENSI TANGGUNG JAWAB SOSIAL PERUSAHAAN KUANSING INTI MAKMUR TERHADAP MASYARAKAT DUSUN TANJUNG BELIT - Miranti, Miranti; Saputra, Angga; Sinaga, Rudi Salam (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aims to find out how the performance of the hamlet government apparatus in carrying out their duties and responsibilities as executors and implementing CSR in Tanjung Belit Hamlet, Jujuhan District, Bungo Regency. Furthermore, what are the Government's obstacles in implementing CSR program activities in the Hamlet. Up to what efforts and steps have been taken to solve the problems that occurred in Tanjung Belit Hamlet. so that later it will become an independent hamlet and have a good future outlook. Capability of Human Resources (HR) is a factor that affects the performance of officials. The problem of the quality of the hamlet government's human resources is an important issue in the implementation of Otoda. Therefore, it is an urgent matter to increase the Human Resources (HR) of the Dusun government, so that the implementation of the Otoda can run as expected, but this is also influenced by two important factors. Level of education In carrying out their duties and responsibilities as hamlet apparatus, especially in providing services and development of hamlet economic growth in general for Tanjung Belit hamlet, it is very much determined by the level of education possessed by the apparatus itself, because the heavier or wider the responsibilities of the hamlet apparatus must be implemented, so officers who have qualified human resources are also needed. Work experience In carrying out duties and responsibilities as a public servant.